2014
DOI: 10.1517/17460441.2014.876988
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic agents in the context of metabolic/bariatric surgery: expanding the scope and impact of diabetes drug discovery

Abstract: Type 2 diabetes (T2D) --particularly with concurrent obesity ('diabesity') --is an intensifying global public-health problem. Medical needs and market opportunities in the T2D space have propelled discovery efforts aimed at inventing new synthetic T2D drugs differentiable by improved safety and efficacy and/ or the ability to modulate emerging T2D targets. Particularly for moderately and severely obese individuals, weight-loss (bariatric) surgery offers an effective means of reducing obesity-driven T2D that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…While partial and total remission rates are high for patients with T2D undergoing metabolic surgery, the beneficial efficacy is not attained in all individuals. Swedish Obese Subjects (SOS) and other clinical trials demonstrated that 20 % to over 40 % of patients did not have T2D remission within 1-2 years post-procedure [14,16] and this value was 11.3 % for 5-year follow-up after RYGB [17]. These patients remain in a hyperglycemic state and need pharmacotherapy [18].…”
Section: Novel Insight Into the Mechanism Of Metabolic Surgery Causing The Diversity In Glycemic Status In Type 2 Diabetesmentioning
confidence: 99%
“…While partial and total remission rates are high for patients with T2D undergoing metabolic surgery, the beneficial efficacy is not attained in all individuals. Swedish Obese Subjects (SOS) and other clinical trials demonstrated that 20 % to over 40 % of patients did not have T2D remission within 1-2 years post-procedure [14,16] and this value was 11.3 % for 5-year follow-up after RYGB [17]. These patients remain in a hyperglycemic state and need pharmacotherapy [18].…”
Section: Novel Insight Into the Mechanism Of Metabolic Surgery Causing The Diversity In Glycemic Status In Type 2 Diabetesmentioning
confidence: 99%